Large Scale Spatial Risk and Comparative Prevalence of Borrelia miyamotoi and Borrelia burgdorferi Sensu Lato in Ixodes pacificus - Padgett, Kerry (Public Library of Science, 2014)

(untitled)
Borrelia miyamotoi is a newly described emerging pathogen transmitted to people by Ixodes species ticks and found in temperate regions of North America, Europe, and Asia. There is limited understanding of large scale entomological risk patterns of B. miyamotoi and of Borreila burgdorferi sensu stricto (ss), the agent of Lyme disease, in western North America. In this study, B. miyamotoi, a relapsing fever spirochete, was detected in adult (n = 70) and nymphal (n = 36) Ixodes pacificus ticks collected from 24 of 48 California counties that were surveyed over a 13 year period. Statewide prevalence of B. burgdorferi sensu lato (sl), which includes B. burgdorferi ss, and B. miyamotoi were similar in adult I. pacificus (0.6% and 0.8%, respectively). In contrast, the prevalence of B. burgdorferi sl was almost 2.5 times higher than B. miyamotoi in nymphal I. pacificus (3.2% versus 1.4%). These results suggest similar risk of exposure to B. burgdorferi sl and B. miyamotoi from adult I. pacificus tick bites in California, but a higher risk of contracting B. burgdorferi sl than B. miyamotoi from nymphal tick bites. While regional risk of exposure to these two spirochetes varies, the highest risk for both species is found in north and central coastal California and the Sierra Nevada foothill region, and the lowest risk is in southern California; nevertheless, tick-bite avoidance measures should be implemented in all regions of California. This is the first study to comprehensively evaluate entomologic risk for B. miyamotoi and B. burgdorferi for both adult and nymphal I. pacificus, an important human biting tick in western North America.